2020
DOI: 10.1007/s00167-020-06083-5
|View full text |Cite
|
Sign up to set email alerts
|

Primary osteoarthritic knees have more varus coronal alignment of the femur compared to young non-arthritic knees in a large cohort study

Abstract: Purpose Many surgeons are performing total knee arthroplasty (TKA) with an aim to reproducing native anatomical coronal alignment. Yet, it remains unclear if primary osteoarthritic and non-osteoarthritic populations have similar knee coronal alignment. This study aims to describe and compare the distribution of femoral and tibial coronal alignment in a large primary osteoarthritic cohort and a young non-osteoarthritic cohort. Methods This is a retrospective analysis of a monocentric prospectively gathered data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(30 citation statements)
references
References 28 publications
4
26
0
Order By: Relevance
“…This study is the first to compare alignment parameters between varus non-arthritic knees and varus OA knees planned for HTO. The wide range of FMA and TMA reported in this study population alludes to a wide variability in knee phenotypes in both osteoarthritic and non-osteoarthritic patients, which is consistent with previous studies that evaluated knee phenotypes [14,24]. Hirschmann et al showed a great variability among knee phenotypes in non-arthritic patients [13][14][15]21].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…This study is the first to compare alignment parameters between varus non-arthritic knees and varus OA knees planned for HTO. The wide range of FMA and TMA reported in this study population alludes to a wide variability in knee phenotypes in both osteoarthritic and non-osteoarthritic patients, which is consistent with previous studies that evaluated knee phenotypes [14,24]. Hirschmann et al showed a great variability among knee phenotypes in non-arthritic patients [13][14][15]21].…”
Section: Discussionsupporting
confidence: 91%
“…This is an important finding which underpins the fact that osteotomy surgeons should question the underlying pathomorphological factors of knee OA and plan patient-specific corrections rather altering what might be normal morphology. This difference in femoral varus between groups was previously reported by Sappey-Marinier et al [24]. In their study, it was found that although the tibial coronal alignment was similar between osteoarthritic and non-arthritic populations, there was a higher degree of femoral varus in the osteoarthritic population.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Our results are supported by two recent studies. Sappey‑Marinier et al described the alignment of 2859 OA patients based on weight-bearing long leg radiographic (LLR) measurements using the functional knee phenotype classification [ 17 ]. They excluded patients with severe bone loss (Ahlbäck classification > 3) and only reported femoral, tibial and knee phenotypes but not functional knee or limb phenotype.…”
Section: Discussionmentioning
confidence: 99%
“… 6 , 7 Thanks to these analyses, several authors have reported that the varus deformity is mainly due to the femoral axis in the osteoarthritic knee. 8 , 9 Indeed, the tibial coronal alignment was similar between osteoarthritic and non-osteoarthritic populations. 8 By contrast, there was a broader and more varus distribution of the femoral coronal alignment in the osteoarthritic population compared to the non-osteoarthritic population.…”
Section: Introductionmentioning
confidence: 89%